In silico analysis of AhyI protein and AI-1 inhibition using N-cis-octadec-9z-enoyl-l-homoserine lactone inhibitor in Aeromonas hydrophila. (January 2022) - Ali, Farman; Cai, Qilan; Hu, Jialing; Zhang, Lishan; Hoare, Rowena; Monaghan, Sean J.; Pang, Huanying
Abstract: AhyI is homologous to the protein LuxI and is conserved throughout bacterial species including Aeromonas hydrophila . A. hydrophila causes opportunistic infections in fish and other aquatic organisms. Furthermore, this pathogennot only poses a great risk for the aquaculture industry, but also for human public health. AhyI (expressing acylhomoserine lactone) is responsible for the biosynthesis of autoinducer-1 (AI-1), commonly referred to as a quorum sensing (QS) signaling molecule, which plays an essential role in bacterial communication. Studying protein structure is essential for understanding molecular mechanisms of pathogenicity in microbes. Here, we have deduced a predicted structure of AhyI protein and characterized its function using in silico methods to aid the development of new treatments for controlling A.hydrophila infections. In addition to modeling AhyI, an appropriate inhibitor molecule was identified via high throughput virtual screening (HTVS) using mcule drug-like databases.The AhyI-inhibitor N-cis-octadec-9Z-enoyl-l -Homoserine lactone was selected withthe best drug score. In order to understand the pocket sites (ligand binding sites) and their interaction with the selected inhibitor, docking (predicted protein binding complex) servers were used and the selected ligand was docked with the predicted AhyI protein model. Remarkably, N-cis-octadec-9Z-enoyl-l -Homoserine lactone established interfaces with the protein via16 residues (V24, R27, F28, R31, W34, V36, D45, M77, F82, T101, R102, L103, 104, V143, S145, and V168), which are involved with regulating mechanisms of inhibition. These proposed predictions suggest that this inhibitor molecule may be used as a novel drug candidate for the inhibition of auto-inducer-1 (AI-1) activity.The N-cis-octadec-9Z-enoyl-l -Homoserine lactone inhibitor molecule was studied on cultured bacteria to validate its potency against AI-1 production. At a concentration of 40 μM, optimal inhibition efficiency of AI-1 was observedin bacterial culture media.These results suggest that the inhibitor molecule N-cis-octadec-9Z-enoyl-l -Homoserine lactone is a competitive inhibitor of AI-1 biosynthesis. Highlights: AhyI is responsible for the biosynthesis of autoinducer-1 (AI-1). In silico methods aids the development of new drugs and treatments for controlling A.hydrophila infections. Selection of AhyI-inhibitor N-cis-octadec-9Z-enoyl-l -Homoserine lactone based on best drug score. To validate its potency against AI-1 production.